Osteopathic manipulative treatment in pudendal neuralgia: A case report. Issue 2 (April 2019) - Origo, D.; Tarantino, A.G.
Abstract: Pudendal neuralgia is characterised by pain in the pudendal dermatome. It could be due to a stenosis of the pudendal canal, a compression along its pathway, or a pelvic trauma. Pudendal nerve entrapment (PNE) syndrome is frequently involved in pudendal neuralgia onset. This case report describes the osteopathic manipulative treatment (OMT) of a patient with functional PNE. A 40-year-old female presented with a 12-month history of intense pelvic pain resistant to 3 months of pharmacologic treatment that arose after three proctological surgeries. A perineal retracted painful scar was visible upon examination. PNE syndrome diagnosis was based on Nantes criteria. The electromyogram of the nerve showed an increased motor response latency of the left pudendal nerve. Visual analogue scale (VAS), female National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI), Oswestry Disability Index (ODI) and Tampa scale of kinesiophobia (TSK) were used to assess patient's symptoms at baseline (T0), after pharmacologic treatment (T1), after OMT (T2), and at 6-month follow-up. Five treatments, including direct and indirect techniques, were performed over 1 month. OMT reduced pelvic neuralgia and disability indexes without any complications, maintaining a positive outcome at 6-month follow-up (VAS: T0 = 10, T1 = 10, T2 = 1.8, T3 = 1.5), (NIH-CPSI: T0 = 34, T1 = 30, T2 = 7, T3 = 6), (ODI: T0 = 48, T1 = 29, T2 = 9, T3 = 5) and (TSK: T0 = 51, T1 = 41, T2 = 20, T3 = 17). This is the first report of a patient diagnosed with functional PNE managed with OMT. A link between PNE, scar and pelvic somatic dysfunctions could suggest double crush syndrome.